"Allow Me to Speak": Stories of Courage Among Immigrant Latina Survivors of Intimate Partner Violence. (November 2017) - Silva-Martínez, Elithet
Intimate partner violence is experienced by millions of women. The experience becomes complex when confronted in a different country, especially for Spanish-speaking Latina immigrants, representing a challenge in their path to survival. This ethnographic study was based in Chicana feminism and Mujerismo epistemology. From the Mujerista framework arises the concept of permítanme hablar and la lucha, which emphasizes the importance of the women's narratives from their own contexts. Consequently, the need of reclaiming from their stories alternative forms of intervention by service providers and those who develop programs as well as social policies in favor of their communities.